COMPARATIVE EVALUATION OF ANTIBACTERIAL EFFICACY OF ALLIUM SATIVUM LINN., ALLIUM AMPELOPRASUM LINN. AND ZINGIBER OFFICINALE ROSCOE. AGAINST METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS - ANANTHAN ANUSWEDHA,; USHA ANANDA RAO, (International Journal of Pharma and Bio Sciences, 2015)
Garlic (Allium sativum L.) and ginger (Zingiber officinale R.) has been used for thousands of years for medicinal purposes. Historically, garlic has been used worldwide to fight bacterial infections.Multi-drug resistant bacteria and their incidence has risen dramatically in recent years. Allium vegetables, particularly garlic (Allium sativum L.) exhibit a broad antibiotic spectrum against both gram-positive and gram-negative bacteria.Methicillin Resistant Staphylococcus aureus (MRSA) are the major cause of nosocomial infections including pneumonia, post-operative wound infection,bacteremia and other infections worldwide. The in vitro antibacterial activity of crude extracts and fresh juice of Allium sativum L. (garlic), Allium ampeloprasum L.(elephant garlic) and Zingiber officinale R.(ginger) was determined and compared against clinical strains of methicillin resistant Staphylococcus aureus. Allium ampeloprasum fresh juice showed maximum inhibition against all the MRSA strains at a concentration of 100µl/ml followed by the fresh juice of Allium sativum.The crude extracts and fresh juice of Zingiber officinale showed no activity at the concentration tested. This study confirms the higher therapeutic potential of Allium ampeloprasum and Allium sativum against MRSA.